Implementation of the Communication Strategy of Bank BPR Bandung Collectors in Reducing the Number of Defaults - Putra, Feby Nugraha; Putri, Sekartaji Anisa (Semantik: Journal of Social, Media, Communication, and Journalism, 2025)
The phenomenon of credit default in the banking sector is concerning in the post-pandemic era, particularly for small-scale financial institutions, such as Rural Credit Banks (BPR). This study analyses the communication strategies used by collectors at Rural Credit Bank (BPR) "X" Bandung to reduce the number of loan arrears. Loan arrears at BPR, caused by factors such as inadequate surveys, debtor dishonesty, or deteriorating financial conditions, pose significant challenges to the bank's financial stability. The purpose of this study is to identify and describe the types and effectiveness of collector strategies, using qualitative methods such as in-depth interviews and observations. Data analysis follows the interactive model by Miles and Huberman. The study reveals that collectors employ a combination of verbal and nonverbal communication strategies, including gentle persuasion and open-ended questions, as well as a calm tone of voice and active listening, all of which are tailored to the debt collection process. These strategies are generally effective, especially the empathetic approach; however, their effectiveness depends on the debtor's characteristics and financial situation. Supporting factors include ongoing training and good internal communication, while barriers include bad intentions from debtors and negative public perceptions. The results of this study concluded that effective communication is crucial in managing problematic loans, and encourage BPR to enhance training, develop ethical guidelines, and promote financial literacy among debtors.